Integrated neuromuscular training intervention applied in schools induces a higher increase in salivary high molecular weight adiponectin and a more favorable body mass index, cardiorespiratory fitness and muscle strength in children as compared to the traditional physical education classes - Vasileva, Fidanka; Font-Lladó, Raquel; Carreras-Badosa, Gemma; Cazorla-González, Jorge; López-Bermejo, Abel; Prats-Puig, Anna (Frontiers in Public Health, 2024)
Background: High-molecular-weight adiponectin (HMW-adiponectin) is a cardio-metabolic health protector. Objectives: 1) to compare body mass index (BMI), cardiorespiratory fitness (CRF) and muscle strength (MS) in healthy school-children depending on their baseline salivary-HMW-adiponectin concentration; and 2) to apply a 3-month integrated neuromuscular training (INT) and evaluate its effects on salivary-HMW-adiponectin concentration, BMI, CRF and MS in the same children. Additional goal: to identify if any potential changes during the 3-month period may be related to a potential change in salivary-HMW-adiponectin concentration. Methods: Ninety children (7.4±0.3years) were recruited in primary schools and randomly allocated into control or intervention group. The intervention consisted of a 3-month INT applied during physical education (PE) classes, twice-weekly, while the control group had traditional PE classes. Body mass and height were assessed, BMI was calculated and HMW-adiponectin was quantified in saliva. To assess CRF and MS, 800m-run and hand-dynamometry were applied respectively. All measurements were performed twice, at baseline and after 3 months. Results: Children with higher baseline salivary-HMW-adiponectin have more favorable BMI (p=0.006) and slightly higher CRF (p=0.017) in comparison to the children with lower baseline salivary-HMW-adiponectin. There were no big changes after the 3-month-period neither in the control, nor the INT group. However, it is worthy to note that the INT induced slightly higher increase in salivary-HMW-adiponectin (p=0.007), and a slightly higher improvement in BMI (p=0.028), CRF (p=0.043) and MS (p=0.003), as compared to the traditional PE classes. Finally, the INT-induced improvement in CRF was associated with the increased post-salivary-HMW-adiponectin concentration (p=0.022). Conclusion: Main findings may suggest the potential utility of an INT as a cost-effective strategy that can be applied in schools to induce cardio-protective effects in school-children.